Position of the rotator cuff footprint in relation to the centre of rotation of the humeral head. (May 2019) - Caruana, Ethan; Wigderowitz, Carlos; Harrold, Fraser
Background: The objective of the present study was to determine the size and position of the rotator cuff moment arms constructed from the cuff footprints, incident on the line of force acting through the humeral head. Methods: Five humeri were dissected, leaving the footprints of the rotator cuff intact. Each of the rotator cuff footprints and the cartilage/calcar interface were digitized and the articular surface was scanned using a high precision surface laser scanner. All of the data were merged into the same coordinate system. The centroid of each cuff footprint, centroid of the articular surface of the humerus (G) and the centroid of the articular surface of the glenoid (P) were calculated. Moment arms were measured as the intersection of a perpendicular line of force from each footprint centroid onto the resultant line of force to the centroid of the Glenoid (P). Results: The mean moment arms of the supraspinatus, infraspinatus and subscapularis muscles were incident close to the centroid (G), whereas teres minor was lateral to the centroid, consistently. Conclusions: The teres minor moment arm aligned distal to the centroid of the sphere, consistently. The results may provide an understanding of the function of each muscle as a mobilizer or stabilizer of the glenohumeral joint. Further investigation is necessary.